Oral Presentations Abstracts: SUPPORTING ETHICAL DECISION MAKING – A TOOL FOR ETHICAL REFLECTION ON CARE TECHNOLOGIES - GRÜBER, Katrin; LOEVSKAYA, Elena (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 The tool FreTiP (Fragen zur ethischen Reflexion von digitalen Technologien in der Pflegepraxis – questions on ethical reflection of digital technologies in nursing practice) was developed in 2020 by the Institute Mensch, Ethik und Wissenschaft (IMEW) as part of ELSI research in the PPZ-Berlin project. Our aim was to develop an instrument that stimulates and supports ethical reflection processes in the application of digital care innovation technologies in practice. Ethical considerations are part of everyday (nursing) life, are closely interwoven with other aspects and are therefore difficult to recognise as such. The starting thesis of our work was that actors in care act on the basis of value concepts that they are more or less aware of. An ethics that is consciously integrated into everyday care takes into account all aspects that are relevant for an action or decision. In this respect, it is important to look at ethics in context and not to understand “ethics” as something isolated, coming from outside. Based on this, the development of the instrument should not consist of “breaking down” ethical concepts and theories to practice, but of ethically locating, structuring and making applicable the experiences, questions and needs of the actors working in nursing practice. Thus, FreTiP is not only to be considered practice-oriented, but also to a certain extent practice-based. The instrument was designed to be suitable for everyday care in clinics, care facilities and in the home context. FreTiP was developed as a low-threshold instrument that can be used flexibly and that takes into account the perspective of patients as well as carers. The development of the instrument was preceded by a triangulated study that included a literature review, interviews and (non-)participatory observations. In the paper, experiences with the ethical reflection tool FreTiP will be presented.